Advanced student motivation in craft teacher education : Learning new yarn crafts at university study courses - Kouhia Anna; Härkki Tellervo (Formakademisk, 2025)
This study investigates student craft teachers’ motivational issues within the course frameworks covering yarn crafts. The data consist of materials gathered from two bachelor-level university courses, which both utilized flipped learning as their pedagogy framework for learning and teaching crafts. Advanced-level student craft teachers participating in the courses (N=15+4) set their own learning objectives to reflect the general course targets defined by the course curriculum. The objectives, self-assessments, course work and course-end surveys were acquired as research data and analysed by thematical qualitative analysis, to obtain knowledge of extrinsic and intrinsic motivations. In line with Self-Determination Theory used as a theoretical framework of the study, the results suggest that possibilities to finetune course objectives to meet students' personal skills and resources were considered crucial for study motivation. Craft learning embraced realization of one’s effort, inner potential  and values, resulting in student satisfaction about receiving personalized attention and instructions for their own study projects. Hence, the results enhance a more detailed understanding of student diversity and related motivational issues that can promote the equity of education.